The Effect of Parenting on The Language Development of Autistic Children - Badi’ah, Atik; Mendri, Ni Ketut; Nugroho, Heru Santoso Wahito; Handayani, Wawuri (Proceeding International Conference on Science and Engineering, 2020)
Autistic children have abilities and characteristics that are different from each other, so different ways of interacting with themselves and the environment and making autistic children as unique individuals (Ginanjar, 2007). The development of autistic children both physically, emotionally, intellectually, and psychosocially has a problem that results in the inhibition of children reaching a level of language development that is appropriate to their age. Parenting in children with autism includes autistic child parents providing emotional, social, informational and practical support. Attention and love from parents and family will encourage autistic children to develop better. An autistic child will feel that he is loved and wanted if more and more people in the family environment who love and care for him. Based on the results of a preliminary study conducted by the author by interviewing 8 autistic schools in the provinces of DIY and Ponorogo, East Java, to 16 parents who have autistic children, the majority of parents (93%) think that by entering autistic children into an outside school ordinary (SLB) autism in accordance with its limitations means their efforts can be said to be enough. Not all parents realize that having children with special needs in accompanying language development can maximize language development. Knowing the effect of parenting on the language development of children with autism This type of quantitative research uses Quasi experiment with the design "Pre test Post test with Control Group Design". Observation was carried out twice. The first observation is to determine the development of an autistic child before being given parenting and the second observation after being given parenting. Sampling was done by purposive sampling with the criteria of parents and autistic children aged 6-12 years in the autistic schools of the provinces of Yogyakarta and Ponorogo, East Java. Examination data were analyzed analytically with the help of SPSS for Windows version 16.0 using paired t-test and Wilcoxon, with a significant level of p <0.05. The experimental group pre-test and post-test with a value of p (sig) 0,000 <0.05 then Ha is accepted and Ho is rejected, meaning there is a difference between pre-test and post-test in the experimental group. In the control group pre-test and post-test with p value (sig) 0.002 <0.05 then Ha is accepted and Ho is rejected, meaning there is a difference between pre-test and post-test in the control group. There is a parenting effect on the language development of autistic children in autistic schools with p (sig) <0.05 means that Ha is accepted and Ho is rejected.